2015
DOI: 10.1073/pnas.1415151112
|View full text |Cite
|
Sign up to set email alerts
|

Natural variations of copper and sulfur stable isotopes in blood of hepatocellular carcinoma patients

Abstract: The widespread hypoxic conditions of the tumor microenvironment can impair the metabolism of bioessential elements such as copper and sulfur, notably by changing their redox state and, as a consequence, their ability to bind specific molecules. S-enriched by ∼1.5‰ in the blood of patients compared with that of control subjects. As expected, HCC patients have more copper in red blood cells and serum compared with control subjects. However, the isotopic signature of this blood extra copper burden is not in favor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
130
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 34 publications
(32 reference statements)
9
130
2
Order By: Relevance
“…It has been demonstrated that, under hypoxic conditions, intracellular Cu was isotopically heavier than under normoxic conditions. This result is in agreement with the enrichment in 65 Cu in the tumor tissue of hepatocellular carcinoma with regard to the healthy surrounding tissue (9), thus suggesting that the tumor hypoxia was at the origin of the difference in Cu isotopic signature.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…It has been demonstrated that, under hypoxic conditions, intracellular Cu was isotopically heavier than under normoxic conditions. This result is in agreement with the enrichment in 65 Cu in the tumor tissue of hepatocellular carcinoma with regard to the healthy surrounding tissue (9), thus suggesting that the tumor hypoxia was at the origin of the difference in Cu isotopic signature.…”
supporting
confidence: 87%
“…The isotopic fractionation of medium-mass endogen elements (i.e., Ca, Fe, Cu, and Zn) has recently been shown to have an outstanding potential for biomedical applications (1). Isotopic fractionation measurements have been identified as new biomarkers for the investigation of metabolic processes (2-6) and as powerful tools for the early detection of diseases (7)(8)(9)(10)(11)(12). Studies of Cu and Zn isotopic fractionation are very promising for the early diagnosis of different types of cancer (9,12) and neurodegenerative diseases (8,13), whereas Fe and Ca isotopic fractionation measurements have shown their ability to monitor Fe absorption efficiency (3) and bone mineral balance (7), respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The calcium serum isotopic composition has been found to have a significant relationship with myeloma (cancer of bone marrow) and implicates a new and needed method to evaluate real-time myeloma-induced bone disease [17]. Four further studies utilising natural isotopic analyses of zinc [18], copper [19][20][21] and sulfur [21] in cancer have emerged recently. Larner et al [18] found an isotopic enrichment in the lighter isotopes of zinc for breast tumours relative to healthy breast tissue in early stage breast cancer.…”
Section: Isotope Fractionation and Cancermentioning
confidence: 99%
“…The single tumourhealthy tissue couple presented by Larner et al shows that this may not be the case for early stage breast cancer, where the tumour tissue is −0.4 ‰ relative to adjacent healthy breast tissue [18]. Balter et al [21] found that both copper and sulfur isotopes of red blood cells were isotopically lighter for HCC patients relative to controls and suggested that sulfur blood isotopic analyses may provide a new diagnostic tool for HCC. The copper isotopic composition of liver tumours was approximately 0.5 ‰ heavier than adjacent healthy tissue.…”
Section: Isotope Fractionation and Cancermentioning
confidence: 99%